Menentukan Tarif Premi Asuransi Kendaraan Bermotor Berdasarkan Data Klaim dengan Distribusi Poisson dan Gamma - Rotua Simamora, Demak; Febriani Sagala, Indah; Kristi Yamin, Yessi (VISA: Journal of Vision and Ideas, 2024)
In calculating premiums based on claim size data obtained from motor vehicle insurance companies, it can be calculated using the Poisson and Gamma distributions. Where in this research, calculations will be carried out on data obtained through research studies and case studies in the form of data on the number and amount of claims from 2011 to 2014 obtained from the official website of the Financial Services Authority. Based on the data collected, there were 59,926,962,942 claims. For the record, find the premium per person every month and year by dividing the premium by the number of life insurance claims from 2011 to 2014, namely 59,926,962,942 claims. The calculation results show that using the moment method with the Poisson-Gamma distribution if the premium is calculated using the pure premium principle, namely 1.25129×106 in a month or 1.5015536893×107 in a year.